Making other worlds possible : performing diverse economies - Roelvink, Gerda, 1978-; St. Martin, Kevin, 1962-; Gibson-Graham, J. K. (University of Minnesota Press, 2015)
There is no doubt that "economy" is a keyword in contemporary life, yet what constitutes economy is increasingly contested terrain. Interested in building "other worlds," J.K. Gibson-Graham have argued that the economy is not only diverse but also open to experimentations that foreground the well-being of humans and nonhumans alike. Making Other Worlds Possible brings together in one volume a compelling range of projects inspired by the diverse economies research agenda pioneered by Gibson-Graham. This collection offers perspectives from a wide variety of prominent scholars that put diverse economies into conversation with other contemporary projects that reconfigure the economy as performative. Here, Robert Snyder and Kevin St. Martin explore the emergence of community-supported fisheries; Elizabeth S. Barron documents how active engagements between people, plants, and fungi in the United States and Scotland are examples of highly productive diverse economic practices; and Michel Callon investigates how alternative forms of market organization and practices can be designed and implemented. Firmly establishing diverse economies as a field of research, Making Other Worlds Possible outlines an array of ways scholars are enacting economies differently that privilege ethical negotiation and a politics of possibility. Ultimately, this book contributes to the making of economies that put people and the environment at the forefront of economic decision making. Contributors: Elizabeth S. Barron, U of Wisconsin-Oshkosh; Amanda Cahill; Michel Callon, École des mines de Paris; Jenny Cameron, U of Newcastle, Australia; Stephen Healy, Worcester State U; Yahya M. Madra, Bogazici U; Deirdre McKay, Keele U; Sarah A. Moore, U of Wisconsin-Madison; Ceren Ŏzselçuk, Bogazici U; Marianna Pavlovskaya, Hunter College, CUNY; Paul Robbins, U of Wisconsin-Madison; Maliha.